2019
DOI: 10.20945/2359-3997000000125
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functions in children with congenital adrenal hyperplasia

Abstract: Objective: There is controversy regarding cognitive function in patients with congenital adrenal hyperplasia (CAH). This study is aimed at the assessment of cognitive functions in children with CAH, and their relation to hydrocortisone (HC) therapy and testosterone levels. Subjects and methods: Thirty children with CAH due to 21 hydroxylase deficiency were compared with twenty age-and sexmatched healthy controls. HC daily and cumulative doses were calculated, the socioeconomic standard was assessed, and free t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Patients with CAH are at risk of some cognitive impairment [ 66 ]; however, the data on cognitive abilities in this population have been controversial [ 66 ]. It was reported that patients with CAH had normal psychometric intelligence but impaired executive functions [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CAH are at risk of some cognitive impairment [ 66 ]; however, the data on cognitive abilities in this population have been controversial [ 66 ]. It was reported that patients with CAH had normal psychometric intelligence but impaired executive functions [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Children and adolescents with CAH are at risk of adrenal crisis with salt loss and hypoglycemia that may negatively impact cognitive performance (Hamed et al, 2018 ). As so, some studies have highlighted the need to assess cognitive functions in children and adolescents with CAH (Amr et al, 2019 ; Hamed et al, 2018 ). However, a newly published study of children and adolescents diagnosed through the neonatal screening program for CAH in Sweden showed normal cognitive abilities (Valeria Messina et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…PedsQL scores were lower for parents’ assessments compared to their children’s, implying a different perception of the impact of their condition; this indicates a need to actively engage patients and parents in the dialogue with multidisciplinary team professionals. School functioning, the lowest scoring category in the PedsQL, may be explained by reduced cognitive function ( 36 , 37 ) or mental health issues ( 4 ). An early diagnosis associates with better cognitive outcomes ( 38 ), a potential explanation being a reduced risk of hypoglycaemia and adrenal crisis.…”
Section: Discussionmentioning
confidence: 99%